Dynamic Change of Lymphocyte-to-Monocyte Is Associated With the Occurrence of POCD After Cardiovascular Surgery: A Prospective Observational Study - Zhao, Qi; Gao, Rui; Liu, Changliang; Chen, Hai; Zhang, Xueying; Guan, Jing; Xie, Xiaoyu; Qiu, Yanhua; Cheng, Xu; Lv, Peilin; Zhu, Tao; Chen, Chan (Frontiers in Behavioral Neuroscience, 2021)
Objective: Postoperative cognitive dysfunction (POCD) is a common and severe complication of cardiovascular surgery. Lymphocyte-to-monocyte ratio (LMR) has been reported to be an independent predictor of lots of diseases associated with inflammation, but the association between the LMR and POCD is not clear. The present study aimed to investigate the potential value of LMR level to predict POCD in patients undergoing cardiovascular surgery. Methods: A prospective observational study was performed on the patients diagnosed as heart diseases undergoing cardiovascular surgeries with cardiopulmonary-bypass. The leukocytes counts were measured by blood routine examination preoperatively. Then we calculated the LMR by dividing the lymphocyte count by the monocyte count. Neurocognitive functions were assessed 1 day before and 7 days after surgery. Perioperative factors were recorded to explore the relationship between LMR and POCD. Results: Totally 75 patients were finally finished the whole study, while 34 patients developed POCD. The preoperative LMR level in the POCD group was higher than that in the non-POCD group. A cutoff value of 4.855 was identified to predict POCD occurrence according to ROC curve. The perioperative dynamic change of LMR level in the POCD group were higher than those in the non-POCD group. A cutoff value of 2.255 was identified to predict POCD occurrence according to ROC curve and the dynamic LMR change was positively correlated with preoperative LMR level. Conclusions: The dynamic change of LMR level in the peripheral blood is associated with occurrence of POCD, and preoperative LMR level seems to be a prognostic biomarker of postoperative cognitive dysfunction in patients after cardiovascular surgery.